2017
DOI: 10.1038/nature23009
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient sensing modulates malaria parasite virulence

Abstract: The lifestyle of intracellular pathogens, such as malaria parasites, is intimately connected to that of their host(s), primarily for nutrient supply. Nutrients act not only as primary sources of energy but also as regulators of gene expression, metabolism and growth, through various signaling networks that confer to cells the ability to sense and adapt to varying environmental conditions1,2. Canonical nutrient-sensing pathways are presumably absent in the causing agent of malaria Plasmodium3–5, thus raising th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(177 citation statements)
references
References 39 publications
7
161
0
Order By: Relevance
“…In addition, blood-stage parasites have to adapt to constantly changing nutrient availability. Recent work has demonstrated that the major energy source for the parasite, glucose, is used as an environmental sensor to modulate progeny number and hence virulence via a signaling cascade 32 . Surprisingly, no effect on transmission was observed under caloric restriction, and glucose complementation did not block sexual conversion in our study 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, blood-stage parasites have to adapt to constantly changing nutrient availability. Recent work has demonstrated that the major energy source for the parasite, glucose, is used as an environmental sensor to modulate progeny number and hence virulence via a signaling cascade 32 . Surprisingly, no effect on transmission was observed under caloric restriction, and glucose complementation did not block sexual conversion in our study 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The maturation of the parasite has also recently been classified based on the transcriptome . Perturbation of the malaria life cycle has now been demonstrated in response to nutrient deprivation, drug treatment, drug resistance, host innate immunity and nutritional status . Given the increasing observation of Plasmodium parasites with altered development within RBCs, advancing models to understand the molecular underpinnings of parasite development and how it is perturbed, is likely to have broad applications.…”
Section: Host Control Of Parasite Proliferationmentioning
confidence: 99%
“…Given that completing the IDC is glucose demanding, malaria parasites may be expected to express genes rhythmically to utilize the energy source efficiently. This could be achieved via the recently discovered nutrient sensing mechanism and that allows parasites to respond to alterations in glucose availability through transcriptional rearrangement 27 . In support of this, genes involved in energy metabolism pathways (glycolysis, fructose and mannose metabolism) showed circadian transcription patterns in the matched parasites while this rhythmicity was lost in mismatched parasites ( Figs.…”
Section: Energy Metabolismmentioning
confidence: 99%